Association of COVID-19 Pandemic and Rate of Cognitive Decline in Patients with Dementia and Mild Cognitive Impairment: A Cross-sectional Study. (March 2021) - Ismail, Ismail Ibrahim; Kamel, Walaa A.; Al-Hashel, Jasem Y.
Introduction: Since the declaration of coronavirus disease 2019 (COVID-19) as a pandemic, patients with dementia, were specifically vulnerable to the negative impact of the outbreak.Objective: To examine the association between lockdown amid COVID-19 pandemic and the rate of cognitive decline among patients with dementia and mild cognitive impairment (MCI).Methods: We conducted a cross-sectional observational study on patients with dementia and MCI who attended the outpatient clinic at Ibn Sina Hospital, the main tertiary neurology center in Kuwait, during the month of September 2020. The rate of cognitive decline, estimated by MMSE scores, was compared between the period prior to, and during lockdown.Results: We evaluated 36 consecutive patients with cognitive impairment (23 females [63.9%], mean age 71 ± 10.8 years, mean disease duration 34.6 ± 29 months). Eleven patients (30.6%) progressed to a more severe stage during the study period; 1 MCI (2.8%) converted to mild dementia, 6 (16.6%) mild to moderate, and 4 (11.1%) moderate to severe dementia. Monthly decline of MMSE scores before lockdown was 0.2 ± 0.1 points, while it was 0.53 ± 0.3 points during lockdown, which was statistically significant ( p  = .001). The most affected cognitive domain was the memory with a mean decline of 1.5 ± 0.8 points.Conclusions: This study provides "real-world" data suggesting rapid cognitive decline in patients with dementia during the lockdown period. Healthcare systems should pay more attention to this vulnerable group, to help them maintain their mental, physical and social well-being during this crisis.